Effects of urbanization on meteorological parameters (MAUSAM, 2004)
In developing countries like India, the urban environment is constantly under stress as a result of migrant population, enhanced energy consumption of the growing population, increased traffic load and industrial activity, deforestation and release of waste products into the atmosphere and hydrosphere. This urbanization coupled with industrialisation affect the urban climate like temperature, precipitation, wind, relative humidity and bright hours of sunshine. Most of the studies are mainly confined to the mid-latitude cities and very little is known about these urban induced changes (except for temperatures) for low latitude cities.There has been a conspicuous increase in the number of industries after 1950 in the cities. Fifteen cities (including four metros) with a population of more than 1 million are selected for this study. Linear trend analysis was carried out over the climatologically data for different meteorological parameters viz., incoming solar radiation, bright hours of sunshine, relative humidity, rainfall, wind speed, total cloud amount and maximum and minimum temperatures. The trends observed in these meteorological parameters are discussed.